Nursing diagnoses in overweight adolescents - Rodrigues, Raphaela Santos do Nascimento; Cavalcanti, Ana Márcia Tenório de Souza; Silva, Telma Marques da (Rev Rene, 2013)
This study aimed to identify nursing diagnoses in overweight adolescents from public schools, according to the International Classification for Nursing Practice. A population-based cross-sectional study that investigated the socio-demographic, behavioural and psychological characteristics of adolescents aged from 10 to 14 years. 11 nursing diagnoses were identified: "Risk of overweight", "Risk of impaired adolescent development", "Risk of insecurity in parental role performance", "Risk of the family impaired ability to manage diet regime", "Risk of impaired ability to manage diet regime", "Risk of lack of knowledge of dietary regime", "Risk of excess food intake", "Risk of negative self-image", "Risk of low self-esteem", "Risk of impaired social well-being" and "Impaired exercise pattern". These diagnoses reflect the multifactorial nature of obesity, highlighting the need for interdisciplinary and intersectoral articulation of nursing interventions for prevention and control of overweight. DOI:https://doi.org/10.15253/2175-6783.20130001000020